Response of sorghum genotypes to anthracnose (Colletotrichum sublineolum) resistance under field conditions in eastern Ethiopia. - Girmay Aragaw; Habtamu Terefe (PLoS ONE)
Sorghum anthracnose is one of the major diseases that have negative impacts on sorghum production in Ethiopia. This study was conducted to evaluate the resistance response of sorghum genotypes against sorghum anthracnose and to determine yield performances of sorghum genotypes under field conditions in two consecutive cropping years. Forty-nine sorghum genotypes were tested for their reactions to anthracnose in the East and West Hararghe Zones, East Ethiopia, during the 2017 and 2018 main cropping seasons. The design of the experiment was laid out in triple lattice square design with three replications. Anthracnose severity was assessed on 16 randomly selected and pre-tagged sorghum plants in the middle two rows of each plot. The eight subsequent times of severity assessments were used to evaluate the response of the genotypes to sorghum anthracnose. The ranges of the mean severity of anthracnose in 2017 and 2018 were 35 to 91% and 38 to 93%, respectively. In 2017 and 2018, the area under disease progress curve varied from 1744 to 3865% of days and from 2354 to 4908% of days, respectively. During the two growing seasons, the genotype ETSL 101469 displayed the highest anthracnose severity, followed by BTX-623. In both experimental years, anthracnose had very strong negative relationships with grain yield and thousand seed weight. The current study demonstrated how Ethiopian sorghum genotypes affect anthracnose development in the field conditions. Throughout the two experimental years, the sorghum genotypes ETSL 100335, ETSL 100395, ETSL 10474, ETSL 100523, ETSL 100498, ETSL 100989, ETSL 100597, and ETSL 101000 continuously exhibited lower disease levels than the other genotypes. Therefore, it is advised to use these genotypes as alternate sources of sorghum anthracnose resistance. Nonetheless, further research across location is necessary to validate their anthracnose resistance in a variety of agro-ecologies.